The durability of Mn–Mo–Sn–W–Sb–O/Ir1–x–ySnxSbyO2+0.5y /Ti oxygen evolution anode for hydrogen production from seawater electrolysis - Bhattarai, Jagadeesh (BIBECHANA, 2012)
New types of electrodeposited nanocrystalline Mn–Mo–Sn–W–Sb–O/Ir1–x–ySnxSbyO2+0.5y/Ti anode is successfully tailored for hydrogen production from seawater electrolysis. Simultaneous additions of tungsten and antimony in an electrodeposited Mn–Mo–Sn–W–Sb–O/Ir1–x–ySnxSbyO2+0.5y/Ti anode are found to be more effective for better durability than that of the electrodeposited Mn–Mo–Sn–O/Ir1–x–ySnxSbyO2+0.5y/Ti anode for long period seawater electrolysis. The examined Mn–Mo–Sn–W–Sb–O/Ir1–x–ySnxSbyO2+0.5y/Ti anode showed nearly 100% oxygen evolution efficiency at the current density of 1000 A.m-2 in 0.5 M NaCl solution of pH 1 at 25°C and it is guaranteed the stable anode performance with 99.7–99.8% oxygen evolution efficiency for more than five months in seawater electrolysis for hydrogen production. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7177 BIBECHANA 9 (2013) 69-74